Women Teachers in the Turbulent Educational World of St. John’s, Newfoundland, 1920-1949 - Whitehead, Kay (The Department of History at the University of New Brunswick, 2008)
This article focuses on the experiences of women teachers in the city of St. John’s between the 1920s and the 1940s. Although their daily work was influenced by many social forces, including those of religion, class, colonialism, and gender, women teachers were positioned as curriculum and pedagogical experts in city schools. They also found spaces to contribute their expertise more broadly to teacher training and education policy-making in Newfoundland during this era. Cet article examine les expériences d’enseignantes de la ville de St. John’s entre les années 1920 et les années 1940. Même si elles subissaient dans leur travail quotidien l’influence de nombreuses forces sociales, dont celle de la religion, de la classe, du colonialisme et du sexe, les femmes enseignantes faisaient figure d’expertes en programmes d’études et en pédagogie dans les écoles de la ville. Elles trouvaient aussi des lieux où elles pouvaient mettre plus largement leur expertise au service de la formation des enseignants et de l’élaboration des politiques en matière d’éducation à Terre-Neuve pendant cette époque.